COMPARISON OF PARAMEDIAN WITH MIDLINE TECHNIQUE OF SPINAL ANAESTHESIA IN ELDERLY: Spinal Anaesthesia - Shehzad, Farrukh; Haider, SM Zaheer; Zafar, Bushra; Malik, Hamza; Jahangir, Muhammad Adil; Kirwan, Saqib (Pakistan Armed Forces Medical Journal, 2018)
Objective: To compare the technique of paramedian with midline approach of subarachnoid block in terms ofnumber of attempts and frequency of success rate in elderly patients undergoing elective lower body surgeries.Study Design: Randomized controlled trial.Place and Duration of Study: This study was carried out at Anaesthesia department of Combined MilitaryHospital Lahore. Six months from Jan 2014 to Jun 2014.Material and Methods: One hundred and seventy elderly patients were scheduled for lower body surgery, usingspinal anaesthesia. They were randomized to either Midline approach (n=85) or Paramedian approach (n=85) bylottery method. The outcome measures number of attempts and success rate were noted in both groups andanalyzed using SPSS version 18.Results: The successful block in first attempt was 95.3% in Paramedian group and 58.8% in Midline group. Meannumber of attempts in paramedian group was 1.24 ± 0.52 as compared to 1.95 ± 0.97 in midline group. A p-value